Analisis Penyeimbangan Beban pada Transformator Distribusi Menggunakan Metode Fuzzy - Suryawan, I Putu Weda; Amrita, Anak Agung Ngurah; Setiawan, Widyadi (Majalah Ilmiah Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2018)
Load Balancing is basically provide the load on the transformer is in accordance with its capacity. Load Balancing is done on a transformer KA 0223 which supported by Bunisari Feeder and powered by the GI Pesanggaran.  A transformer is located on Kubu Anyar Street Legian Kuta with the installed capacity of 200 kVA. The Transformer brand used is Starlite. The number of customers in a transformer KA 0223 as much as 173 customers. Measurement of load current is done at peak load that is at night. The data of measurement result then processed using Fuzzy method to get balanced result, the percentage of unbalance of load according to ANSI / IEEE Std 446-1987 is 5% and to know the point of customer that must be added or subtracted. The data used in 2015 are in January and June, 2016 in January and June, in 2017 in January.  Measurement results in the year 2017 January 1st semester percentage of load unbalance before using the Fuzzy method of 13.5%. After using the Fuzzy method, the percentage of load unbalance is much better than before at 2.5%. The measurement result of 2015 in 2sd semester is said to be balanced, because the percentage of load unbalance is equal to 5%. After using Fuzzy method, the percentage of load unbalance is much better than before that is equal to 2.2%. This proves that the program can work when the system is either balanced or not.